HE RELATIONSHIP BETWEEN LONELINESS LEVEL AND DECEPTION TENDENCIES IN MARRIED INDIVIDUALS - Kumcagiz, Hatice; Demir, Yasin (My University, 2020)
This study was conducted to investigate the relationship between the level of loneliness and the tendencyto deceive in married individuals. 270 volunteer married individuals participated in the study. The data of thestudy were collected by using the Deception Tendency Scale and UCLA Loneliness Scale and the analyzeswere performed through SPSS package program. Results show that males' tendency to deceive is significantlyhigher than females, and loneliness level does not differ significantly according to gender. Both the tendencyof deception and loneliness levels of the individuals who had multiple marriages were significantly higher thanthe individuals who had single marriages. In addition, there was a positive relationship between loneliness andtendency to deceive. Finally, it was found that the tendency to deceive predicts loneliness to a meaningful level.
Keywords: Psikoloji; Aile Çalışmaları